Klasifikasi Daya Tarik Wisata Unggulan Provinsi Bengkulu Sebagai Upaya Menyongsong Visit 2020 Wonderful Bengkulu - Dwi Oktavallyan Saputri; Zamdial Ta’alidin; Atik Prihatiningrum (Magister Tourism Study, Faculty of Tourism, Udayana University, 2019)
Bengkulu Province has begun to aware to its tourism potential, hence a program called